50. SURVEY ON THE KNOWLEDGE AND ATTITUDES OF PSORIASIS PATIENTS TOWARDS ARTIFICIAL INTELLIGENCE APPLICATIONS (Vietnam Journal of Community Medicine, 2026)
Objective:  To survey the knowledge and attitudes of psoriasis patients towards artificial intelligence applications.Subjects and Methods: A cross-sectional descriptive study was conducted on 309 psoriasis patients at the National Hospital of Dermatology and Venereology from February 2024 to May 2024.Results: The majority of patients (91.9%) were unaware of AI applications. Most patients trusted AI diagnosis only if it was confirmed by a specialist doctor, with a consensus of 70.6%. The perceived benefits of AI include providing data for medical research, improving diagnostic accuracy, and increasing access to healthcare services. The three biggest obstacles were patients' uncertainty about using AI (72.1%), difficulty in use (68.4%), and lack of time (49.0%). Regarding the use of AI applications to diagnose psoriasis, 64.7% of patients considered this application useful. However, only a small proportion (18.4%) expressed a willingness to use the AI application. The level of understanding of the patients is closely related to their educational level and age.Conclusion: Due to the low level of understanding and trust in AI among psoriasis patients, they were not inclined to use AI applications. However, patients believed that using AI for diagnosing psoriasis via clinical images was useful. This indicates the need for better education and clarification about the benefits of AI technology in dermatology to improve patient acceptance and utilization.
Keywords: survey, knowledge, artificial intelligence, psoriasis.